The character of teaching practices in a teacher education institution: findings from observation checklist - Eng Tek Ong, Abdul Rahman Nurulhuda, Wahid Rosdy, Mohd Tajudin Norain, Abd Samad Yahya Razak, Mazuwai Azwani, Kosni Ahmad Nazri, (Universiti Pendidikan Sultan Idris, 2017)
The character of teaching practices in a teacher education institution: findings from observation checklist by Eng Tek Ong, Abdul Rahman Nurulhuda, Wahid Rosdy, Mohd Tajudin Norain, Abd Samad Yahya Razak, Mazuwai Azwani, Kosni Ahmad Nazri,